Development and Implementation of HVAC-KBCD: A Knowledge-Based Expert System for Conceptual Design of HVAC&R Systems-Part 1: General Framework - Maor, Itzhak H; T Agami Reddy (ASHRAE transactions, 2004)
The typical HVAC&R design process involves generating a relatively small number of alternative solutions (configurations of systems, subsystems, and components) and then utilizing analysis and estimation tools to select a "best" solution based on predefined selection criteria, for example, lowest lifecycle cost. This approach is limited by the engineer's experience, capabilities, and time constraints, often resulting in missed opportunities for optimum system selection. Further, the latest equipment, design approaches, and concepts are often not even considered. As a result, the overall design process is being gradually compromised. A knowledge-based expert system (KBES) can augment the capability of current advanced building simulation tools by creating the necessary means for automatically generating, analyzing, and sorting numerous design solutions subject to both site and user constraints. This paper describes the general framework of such a KBES called HVAC-KBCD (knowledge-based conceptual design), capable of automatically synthesizing the complete set of possible HVAC&R systems, which can then be analyzed using available building energy simulation programs such as DOE-23E. This synthesis is done by first pruning or shrinking the solution space of the design alternatives by applying static expert knowledge (Level 1) and then by a guided search dominated by dynamic application knowledge (Level 2). Level 1 starts with a database of all feasible secondary systems (and another for all feasible primary systems) and uses assembly rules and application rules based on heuristics expert knowledge, design practice, and standards to generate the permissible design alternatives of secondary systems (and primary systems). Level 2 uses initiation rules along with matching rules to combine secondary systems among themselves (since the building has different zones) and with primary systems. These capabilities have been programmed into a commercial hybrid KBES shell along with procedural programming capabilities that have the ability to perform simple heuristic cooling and heating design load, as well as f rst and maintenance cost calculations. ANSI/ASHRAE/IESNA Standard 90.1-2001 has been used to set the minimum allowed energy performance for equipment such as fans, chillers, boilers, etc. This paper describes the general framework, structure, capabilities, and inner working of the HVAC-KBCD, while a companion paper will illustrate and demonstrate the entire methodology described here to the conceptual design of office buildings.